Hero dog! - Lysiak, Hilde, 2006-; Lysiak, Matthew; Lew-Vriethoff, Joanne (2017)
Nine-year-old Hilde Lysiak is an aspiring reporter with her own newspaper, the Orange Street News, and she is investigating break-ins and missing baked goods--and with the help of Zeus, a little dog with a big bark, she intends to track down the thief who is trying to steal a win in the Bake-Off Bonanza, one of Selinsgrove's biggest events
Appeals to 2nd-3rd graders
Reading level grade 2
Keywords: Reporters and reporting -- Juvenile fiction; Theft -- Juvenile fiction; Dogs -- Juvenile fiction; Children$1 (Bs bookss; Fiction; Detective and mystery fiction; Detective and mystery fiction; Fiction; Juvenile works